The effect of liquid CO2 treatment on surface properties of ultrafine coal. Issue 8 (18th April 2018) - Zhang, Wenjun; Dai, Xiaoyun; Li, Weiming; Luo, Shunfa
ABSTRACT: In order to understand the influence of liquid CO2 on ultrafine coal surface properties, the experiments of coal surface modification by liquid CO2 were performed in a column agitator. Fourier Transform Infrared Spectroscopy, X-ray Photoelectron Spectroscopy, and microcalorimeter were used to analyze the variation of surface functional groups and wetting heat. The results show that liquid CO2 could change the percentage of hydrophilic and hydrophobic functional groups. The mineral particles with liquid CO2 penetrate into the pore of ultrafine coal, covering the inner surface and result in the increase of wetting heat.